Prevalence of C-shaped canals in mandibular second molars in a Kerman population - Maryam Kuzekanani; Malek Bahmani (Isfahan University of Medical Sciences, 2011)
Introduction: Knowledge of the possible internal anatomy and morphology of the root canal system of the teeth is a key factor in successful root canal treatment. The aim of this investigation was to determine the prevalence of C-shaped canals in mandibular second molars of a Kermani population.Materials and Methods: In this in vitro cross-sectional study, 200 extracted mandibular second molars were collected from several health service centers in Kerman city. Access cavities were prepared on occlusal surfaces of the teeth and the pulp tissue was removed by immersing the samples in 2.5% sodium hypochlorite for 12-24 hours. Then the teeth with C-shaped canals were separated and cross-sections were prepared at CEJ, mid-root and apical portions of the canals using a diamond disk. The C-shaped canals were classified according to the method introduced by Haddad in 1999. Data were analyzed using descriptive analysis (α = 0.05).Results: Of the total of the samples ten teeth showed C-shaped canals (5%). Two teeth (1%) belonged to category I (true C-shaped); five teeth (2.5%) were from category II; one tooth (0.5%) was from category III and one tooth (0.5%) was C-shaped at CEJ, with the canals separating at mid-root and ending in three separate apical foramina.Conclusion: According to the results of this study, the prevalence of C-shaped canals was 5% in the Kermani population under study, which is consistent with reports from all other parts of the world. Key words: C-shaped canal, Prevalence, Molar, Tooth, Kerman.